Multidisciplinary health care in cases of childhood suicidal ideation: operational and organizational limits - Karina Alcântara de Sousa; Maria Goreth Silva Ferreira; Edna Ferreira Coelho Galvão (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to know the health care process performed by the multidisciplinary team in cases of suicidal ideation for children and adolescents in Primary and Secondary Care. Methods: a descriptive study with a qualitative approach carried out with 12 professionals from ESFs, EACS and CAPS II in the city of Santarém. The software IRAMUTEQ 0.7 alpha 2 was used to build the similarity tree and analyze speech content. Results: the word "no" is present prominently in the interviewees' speeches about experiences and strategies for coping with suicide, revealing an absence of individual preparation and structure in the segments of SUS Primary and Secondary Care. Final considerations: health team assistance finds operational and organizational limits during the implantation of intervention strategies and coping with the factors that trigger child and youth suicide. It is important to make specific resources feasible, to organize reference protocols and support programs for patients and families.